AKULTURASI BUDAYA ISLAM DAN JAWA DALAM TRADISI MENGUBUR TEMBUNI - Siti Humairoh; Wildan Zulza Mufti (UIN Antasari Banjarmasin, 2021)
This article analyzes the acculturation of Islamic and Javanese culture in the tradition of burying tembuni in the Panti community. This study aims to determine the construction of the community in understanding the history of the burial of the Tembuni tradition, the meaning of the forms and symbols of the rituals of the community in the burial of the Tembuni tradition and how the values contained in the tradition. This type of research is descriptive qualitative, using an ethnographic approach with observation, documentation, and in-depth interviews. The results of this study are that there are no special records regarding this tembuni burial tradition, both in terms of when and who first triggered it. Where in this ritual there are elements of Hindu-Buddhist belief, kejawen and finally intersect with Islam, which in this process the author calls the process of cultural acculturation. Tradition in the ritual of burying tembuni has existed since ancient times and nothing has changed, for centuries. Therefore, it has become a consideration related to the form of rituals and symbols that are believed to have a sacred value by the Panti community. So that this can have sociocultural implications and a strong relationship with the future of children in community life in the future. The tradition of burying the tembuni seeks to reveal the relationship between humans and God through prayer, rituals as a mediation to express gratitude and ask for salvation. This tradition contains values that are meaningful to the Panti community, such as religious values, moral values, and social values. Artikel ini menganalisis tentang akulturasi budaya Islam dan Jawa dalam tradisi mengubur tembuni di masyarakat Panti. Penelitian ini bertujuan untuk mengetahui konstruksi masyarakat dalam memahami sejarah penguburan tradisi Tembuni, makna bentuk dan simbol ritual masyarakat dalam penguburan tradisi Tembuni dan bagaimana nilai-nilai yang terkandung dalam tradisi tersebut. Jenis penelitian ini adalah deskriptif kualitatif, menggunakan pendekatan etnografi dengan observasi, dokumentasi, dan wawancara mendalam. Hasil dari penelitian ini bahwa tidak ada catatan khusus mengenai tradisi penguburan tembuni ini, baik dari segi kapan dan siapa yang pertama kali memicunya. Dalam ritual ini terdapat unsur kepercayaan Hindu-Budha, kejawen dan akhirnya bersinggungan dengan agama Islam, yang dalam proses ini penulis sebut sebagai proses akulturasi budaya. Tradisi dalam ritual mengubur tembuni sudah ada sejak zaman dahulu dan tidak ada yang berubah, selama berabad-abad. Oleh karena itu, telah menjadi pertimbangan terkait bentuk ritual dan simbol-simbol yang diyakini akan nilai kesakralitasnya oleh masyarakat Panti. Sehingga hal tersebut dapat berimplikasi pada sosiokultural dan hubungannya yang kuat dengan masa depan anak dalam kehidupan masyarakat kelak. Tradisi mengubur tembuni ini berupaya mengungkap hubungan manusia dengan Tuhan melalui sembahyang, ritual sebagai mediasi untuk mengungkapkan rasa syukur dan meminta keselamatan. Tradisi ini mengandung nilai-nilai yang bermakna bagi masyarakat Panti, seperti nilai-nilai religius, nilai moral, dan nilai sosial.